2000
DOI: 10.1152/ajpregu.2000.278.1.r60
|View full text |Cite
|
Sign up to set email alerts
|

Fluid extravasation from spleen reduces blood volume in endotoxemia

Abstract: We recently demonstrated that fluid is filtered out of the splenic circulation and into the lymphatic system. The current experiments were designed to investigate the importance of this route of fluid extravasation in endotoxemia. Lipopolysaccharide (LPS) was infused into conscious intact and splenectomized rats (150 microg x kg(-1). h(-1) i.v. for 18 h). In the intact rats, mean arterial pressure (MAP) fell from 101+/-2.4 to 88+/-3.9 mm Hg (n = 7) and then stabilized at about 90 mm Hg. Hematocrit rose from 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 28 publications
1
25
0
5
Order By: Relevance
“…They have found that the spleen has a very high blood flow (∼8 ml/min/g) (20), and also that there is a significant arteriovenous volume difference that is filtered out of the blood into the lymphatic system (2,20). Such filtration is exaggerated during volume loading (2) and LPS infusion (21), favoring lymph formation even further in these conditions. In line with these observations, we found that spleen lymph accumulated avidly at a rate of ∼2 ml/min in control situation and increasing 8-fold this value 3 h after LPS exposure.…”
Section: Discussionmentioning
confidence: 99%
“…They have found that the spleen has a very high blood flow (∼8 ml/min/g) (20), and also that there is a significant arteriovenous volume difference that is filtered out of the blood into the lymphatic system (2,20). Such filtration is exaggerated during volume loading (2) and LPS infusion (21), favoring lymph formation even further in these conditions. In line with these observations, we found that spleen lymph accumulated avidly at a rate of ∼2 ml/min in control situation and increasing 8-fold this value 3 h after LPS exposure.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that intrasplenic fluid extravasation plays a critical role in the early stages of endotoxemia-induced hypovolemia and hypotension (Andrew et al 2000;Andrew and Kaufman 2001a). Lipopolysaccharide (LPS) infusion, a model of endotoxemia, was shown in conscious rats to cause profound reductions in mean arterial pressure and plasma volume.…”
Section: Pathophysiology-intrasplenic Fluid Efflux In Septic Shockmentioning
confidence: 99%
“…A nonocclusive cannula (Silastic, ID: 0.51-mm, OD: 0.94-mm) was implanted into the inferior vena cava for drug infusion [15]. A pressure transmitter (PA-C40, Data Sciences International) was implanted in the abdominal aorta [2]. Animals were allowed to recover for one week from surgery and to regain their preoperative body weight.…”
Section: Surgerymentioning
confidence: 99%